Análisis de la estructura narrativa gráfica de la serie de cómic X-Men de los años 60' al 90' en relación al concepto de cultura popular americana (2018)
Taking into account the comic as a narrative resource of graphic essence in which a story is represented, which has had great relevance to represent features of popular culture to which the authors belong, knowing the X-Men as part of In this narrative universe, this research was carried out in order to analyze the graphic narrative structure of the X-Men comic series from the 60's to the 90's in relation to the concept of American popular culture.    To do this, we used the qualitative descriptive methodology, where we took numbers published between the 60s and 90s, from the series No. 1 to 280, choosing the following: # 1, 141, 142 and 227.   Based on theories presented by authors such as Umberto Eco, Claudio Lobeto, Eliseo Verón, Will Eisner, Alipio Sánchez and Carl Jung, among others, an approach was made to concepts such as popular culture, graphic narrative, social discourse, interinfluence and the theory of the archetypes, which served for the analysis through a template of the narrative discourse of the selected X-Men.     In this analysis, the technical sheet of the comic was taken into account, starting from the cover, with data such as the publishing house, date of publication, writers, editors, number of pages, main and secondary characters, etc., the extratextual analysis allowed evidence the historical context that gave rise to the events and stories told, with which it was possible to determine the elements of American popular culture that were highlighted or used in the comic; the textual analysis that gave an account of the sequences, planes, elements of language, onomatopoeias, transtextual analysis, made reference to the narrative function and important references about the social icons of the moment, clothing, cars, popular characters mentioned, historical facts , etc.     Through this analysis it was concluded that the X-Men comic is a clear sample of American culture, where the writers and cartoonists number by number have been responsible for telling a story, characterized by being a cartoon that refers to historical moments that They impacted the United States, which range from historical events such as assassinations and attacks to presidents, bomb threats, wars, through lifestyles, the eccentricities of the powerful, fashions, to the struggle of warrior peoples like the American Indians . All this is what makes this comic special and emphasizes, because people feel identified, both those of the era where it was written and those of the current era